Biofilms in drinking water: problems and solutions - Simões, Lúcia C. (2013)
The main goal of water companies is to deliver to each consumer microbiologically safe drinking water (DW), adequate in quantity and delivery pressure and acceptable in terms of taste, odour and appearance. Drinking water distribution systems (DWDS) are known to harbour biofilms, even in the continuous presence of a disinfectant. These biofilms are a source of planktonic bacteria, which will remain present when the water is delivered through a consumer’s tap. The presence of biofilms in DWDS constitutes one of the currently recognized hazards affecting the microbiological quality of the product and may lead to a number of unwanted effects on the organoleptic quality of the distributed water. Importantly, biofilms constitute a persistent reservoir of pathogenic microorganisms, which are responsible for several waterborne diseases. Antimicrobial products, particularly chlorine, have been the main weapons used to disinfect DW. Although this strategy is widespread, there are not yet standardized disinfection strategies with reliable efficacy in the control of biofilms. This review covers the advances in the knowledge of public health problems caused by the presence of biofilms in DWDS and the current strategies for DW disinfection and associated biofilms.